The Impact of COVID-19 Pandemic on Spirituality of Muslim and Christian Youth in Banjarmasin - Dewi Agustina; Basrian; Muhammad Sandi Rosyadi (Religi: Jurnal Studi Agama-agama, 2023)
COVID-19 cases in South Kalimantan have reached a peak of the most cases, specifically around 70 thousand cases in 2021. The data had shown that there were new obstacles and challenges for the youngsters to maintain their spirituality and religiosity. Initially, the youngsters could participate in religions and spiritual congregate traditions, but during the pandemic all of these activities were restricted. This research aims to find out the pattern of Muslim and Christian youth’ religious worship activities that were felt during the COVID-19 pandemic in Banjarmasin and knowing the increase or decrease in spirituality. This research uses field research with phenomenological approach. This research concludes the pattern of worship activities for Muslim youngsters’ increases in terms of quantity, but for the Christian youngsters the sense of togetherness in worship tends to decrease because it is carried out by virtual meeting. The COVID-19 pandemic has a deep meaning for some of them that is being able to spend more intensive time with their family. The impact of COVID-19 on spirituality of the youngsters has increased, normal and decreased from prayer fulfilment, universality and connectedness aspect Keyword: COVID-19 in Banjarmasin; Spirituality; Muslim; Christian